A comparative study of Jarak Towo cassava farming in the mountainous areas of Karanganyar Regency in supporting the availability of raw materials for food processing industry. Issue 1 (November 2021) - Irianto, H; Mujiyo; Qonita, A; Riptanti, E W; Ningsih, H
Abstract: Cassava is a commodity that is commonly marginalized. However, jarak towo cassava is exceptional as this variety has a large market potential with a more competitive price. However, only a few farmers are aware of this business potential. This study aimed to conduct a comparative study of the cropping patterns of jarak towo cassava to investigate the farmers' income or profit more thoroughly. This study was carried out in three sub-districts, including Jatiyoso, Tawangmangu, and Ngargoyoso, the respondents were taken using snowball sampling, with 20 respondents from each sub-district. The results showed that farmers in Ngargoyoso Sub-district spent the highest total cost. Meanwhile, farmers in Jatiyoso Sub-district received the highest income and profit. The highest efficiency was shown by farmers in Jatiyoso, while the lowest efficiency was performed by farmers in Tawangmangu. These findings depict how farmers develop jarak towo cassava farming in meeting the market demand.